Islamisme Turki: Kaum Tarekat dan Kebangkitan Islam-Politik Republik Turki - Mahendra, Fahmi Rizal (State Islamic Institute of Kudus (IAIN Kudus), 2021)
After announcing as an independent state, the Republic of Turkey adopted the secularism system as the principle of the new Turkish state. In simple terms, the Turkish state released the Islamic identity that had been attached and identical to the Ottoman Turkish empire which had lasted for 700 years. In implementing the secularism policy, the Turkish government faces challenges from Muslims / Islamists who want to build secularism by carrying out rebellions or participating in elections with the aim of restoring sharia or wanting to establish an Islamic state again. This study aims to trace the roots of Turkish Islamism in the modern period or after the founding of the Republic of Turkey. By using historical research methods and the use of qualitative methods. This study found several factors that influenced the rise of Turkish Islamism. One of them is the vital role of the tarekat centered in the Iskenderpasa Mosque, led by Sheikh Mehmet Zahid Kotku. In an effort to fight secularism, the tarekat mobilized their members to take an active part in the elections in Turkey. Many of the tarekat members, especially the Naqshbandiyah who occupy important positions in Turkey, such as Turgut Ozal, the former President of Turkey, Erbakan, the former Prime Minister of Turkey, one of the important actors in the rise of the current Islamic Party, Recep Tayyib Erdogan, are also members of the congregation of the Naqshbandiyah Order.